Improving the mechanical, wear and anti-corrosion performance of polyester coating on structural steel by graphite addition - Najoua Barhoumi; Abdelkarim Ghanem; Mariem Koudhai; Kaouther Khlifi; Mohamed Ali Terras (eXPRESS Polymer Letters, 2022)
Organic polymer coatings have been extensively used for painting in industrial applications to prevent the deleterious effects on the metallic components. In this study, electrostatic polyester coatings with two amounts of graphite (5 and 10 wt% Gr) were deposited on structural steel substrate. The effect of Gr addition on the microstructure, mechanical, adhesion and tribological behavior were characterized using SEM, EDS, XRD, nano-indentation and scratch test. The coatings’ resistance to corrosion was investigated using electrochemical measurements in 3.5 wt% NaCl solution. According to the results, the Gr particles were homogeneously distributed throughout the polyester coatings. The hardness and elastic modulus of the polyester coatings increased from ~0.23 and ~6.7 to ~0.68 and 10.9 GPa upon increasing the Gr contents from 0 to 10 wt% Gr, respectively. Moreover, the friction coefficient decreased from ~0.5 to ~0.2. The results also showed an attenuation of the severe wear mechanism and a reduction of the plastic deformation. Consequently, the wear resistance improved by three times due to the lubricating role of Gr. All the coatings showed a high adhesion level to the steel substrate with a cohesive critical load higher than Lc1 = ~7 N and an adhesion strength greater than σc = ~215 MPa. The incorporation of Gr allows high protection of the steel against corrosion due to their barrier role.